Effectiveness of a Structured Educational Intervention on Managing Minor Disorders of Pregnancy Through Home Remedies Among Antenatal Women in Urban and Rural Kuppam - S. Vinoli (International Journal of Midwifery Nursing And Practices, 2026)
Pregnancy is a physiological process often accompanied by minor disorders such as nausea, vomiting, backache, heartburn, and fatigue, which can affect the well-being of expectant mothers. Appropriate knowledge and timely management using simple home remedies can significantly reduce discomfort and improve maternal health. This study aimed to evaluate the effectiveness of a structured educational intervention on the management of minor disorders of pregnancy through home remedies among antenatal women in urban and rural areas of Kuppam. A quasi-experimental comparative research design was adopted, involving antenatal mothers attending selected urban and rural health clinics. Participants were assessed for their baseline knowledge regarding minor pregnancy disorders and their home-based management using a structured questionnaire. Following the pretest, a structured educational programme was administered, covering common minor ailments and safe, evidence-based home remedies. A posttest was conducted after the intervention to evaluate changes in knowledge levels. The findings revealed a significant improvement in posttest knowledge scores among participants in both urban and rural groups, indicating the effectiveness of the educational intervention. Furthermore, a comparative analysis showed variations in baseline knowledge between the two groups, with rural participants demonstrating relatively lower initial awareness. However, both groups exhibited substantial gains following the intervention. The study highlights the importance of structured teaching programmes in empowering antenatal mothers with practical, cost-effective strategies to manage minor pregnancy-related discomforts safely at home. Incorporating such educational initiatives into routine antenatal care services can enhance maternal self-care practices and overall pregnancy experience.
Keywords: Structured educational intervention; antenatal mothers; home remedies; maternal health education; minor disorders of pregnancy